Implementation of Differentiation Learning in the Independent Curriculum for Learning PJOK Subjects at SMA Negeri Kota Pematangsiantar - Putra, Wahyu Ade; Nasuka; Irawan, Fajar Awang (Universitas Negeri Semarang, 2024)
Implementation of the concept of Merdeka Belajar which guarantees freedom for educators in formulating learning designs and assessments according to student characteristics and all mapping of student needs through the application of differentiated learning. The purpose of this study is to analyze the knowledge and implementation of the differentiation learning approach used by PJOK teachers at SMA Negeri Kota Pematangsiantar. This research is qualitative research with observational data collection techniques, interviews and documentation. This research was conducted in 6 public high schools in Pematangsiantar City. The sample in this study consisted of 6 principals, 6 teachers and 24 students. The data analysis technique used in this study is the data analysis of the Miles and Huberman model. The results showed that PJOK teachers in 4 Pematangsiantar City State High Schools had succeeded in implementing differentiation learning well, while the other 2 high schools had not done so. The conclusion of this study is that educators have made initial preparations with diagnostic assessments and selected differentiation of content, processes, or products according to student interests and talents. The positive impact of differentiated learning is felt by both educators and learners, although there is a negative impact in the form of student boredom on some learning topics due to the lack of variety in teaching methods. The recommendation for future research is to analyze differentiation learning at the private and public high school levels as a whole.